2020
DOI: 10.3389/fimmu.2020.590558
|View full text |Cite
|
Sign up to set email alerts
|

Case Series: Gene Expression Analysis in Canine Vogt-Koyanagi-Harada/Uveodermatologic Syndrome and Vitiligo Reveals Conserved Immunopathogenesis Pathways Between Dog and Human Autoimmune Pigmentary Disorders

Abstract: Vogt-Koyanagi-Harada syndrome (VKH) and vitiligo are autoimmune diseases that target melanocytes. VKH affects several organs such as the skin, hair follicle, eyes, ears, and meninges, whereas vitiligo is often limited to the skin and mucosa. Many studies have identified immune genes, pathways and cells that drive the pathogeneses of VKH and vitiligo, including interleukins, chemokines, cytotoxic T-cells, and other leukocytes. Here, we present case studies of 2 canines with VKH and 1 with vitiligo, which occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 83 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…One study indicated that rs4946936 of the FOXO3A gene might be associated with susceptibility to vitiligo, especially active vitiligo, and FOXO3A levels were decreased in vitiligo patients compared with normal controls [ 17 ]. Another study reported the downregulation of FOXO1 in vitiligo lesional skin [ 18 ]. Integrins are proteins that link the cell cytoskeleton to the extracellular matrix (ECM) mechanically and biochemically.…”
Section: Discussionmentioning
confidence: 99%
“…One study indicated that rs4946936 of the FOXO3A gene might be associated with susceptibility to vitiligo, especially active vitiligo, and FOXO3A levels were decreased in vitiligo patients compared with normal controls [ 17 ]. Another study reported the downregulation of FOXO1 in vitiligo lesional skin [ 18 ]. Integrins are proteins that link the cell cytoskeleton to the extracellular matrix (ECM) mechanically and biochemically.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many other factors, including intestinal flora, viral infection, and genetic factors, are involved. 3 Among these factors, the intestinal flora has received increasing attention. It has been recognized that intestinal flora is related to some autoimmune diseases, such as Behcet disease, rheumatoid arthritis, and inflammatory bowel disease.…”
mentioning
confidence: 99%
“…Specifically, as in active SLV, the loss of choroidal melanocytes is associated with an INF-γ polarized, Th1 cell-mediated immune response and aberrant melanocyte function. The immunopathogenesis in SL vision impairment resembles induced uveitis and human ocular diseases, especially Vogt–Koyanagi–Harada syndrome and sympathetic ophthalmia, both of which are autoimmune disorders associated with vitiligo ( 7 , 32 34 ). Hence, the Smyth chicken model provides the opportunity to expand our understanding of spontaneous autoimmune pigmentation disorders, including autoimmune pigmentation loss associated with melanoma therapy ( 35 ), and develop effective treatment and prevention strategies.…”
Section: Discussionmentioning
confidence: 99%